Graikų ir lotynų kirčiavimo įtaka lietuvių kirčio žymėjimui - Strockis, Mindaugas (Baltistica, 2004)
THE INFLUENCE OF GREEK AND LATIN ACCENTUATION ON LITHUANIAN ACCENT NOTATION The accent signs of most alphabetic languages ultimately derive from Greek signs devised in the 3rd century BC. This ’Alexandrine’ system of accent notation was transformed into the now current ‘Byzantine’ system for Greek around 400 AD. The Greek circumflex, originally written in the form of an arc like an inverted breve, was graphically transformed into its present wavy shape (identical to the Latin tilde) some time in the Middle Ages. In 16th century Europe (not in the 17th century, as was earlier believed) an artificial, so-called ‘Henninian’, accentuation system of Greek arose. In consequence, Greek accent signs were often treated as meaningless diacritics, useful only for the distinction of otherwise homonymous word forms. A similar use of distinctive (phonetically meaningless) accents was created in the Latin script, where it was current from the late 16th to the late 18th century. The Lithuanian accentuation of Daniel Klein follows closely this humanist Graeco-Latin usage of distinctive diacritics. The same tendency is observed in other Lithuanian writings of the time as well. The genitive singular endings -ôs / -ês and genitive plural ending -û were therefore more or less regularly marked with a circumflex sign, which had, at least in printed texts, the Latin angled (not the Greek tilde-like) shape. Thus the written circumflex sign, be it by incidence or, as Kurschat suggests, as a result of the intuitive insight of old Lithuanian grammarians, coincided with the actual Lithuanian circumflex intonation; accordingly the acute sign came to denote the Lithuanian acute intonation. The actual Lithuanian accents were, however, greatly distorted in writing by formally applying Greek accentuation rules. The accent notation of the 1737 grammar Universitas Lingvarum Litvaniae, known for its exact adherence to the actual Lithuanian syllable intonations rather than to formally applied Greek rules, is nevertheless consistent with this Graeco-Latin tradition in its choice of the circumflex sign to mark the Lithuanian circumflex accent. In the printed 1737 book the accent notation appears, however, somewhat awkward – an accentless letter of a different typeface is substituted for a letter with the acute – but we argue that this oddity was not the original author’s intention but was due to the lack of accented letter punches at the Vilnius University printing house. The alternative tradition of Lithuanian accent notation, started by Simonas Stanevičius, adopted by Kazimieras Jaunius, and rejected by Kazimieras Būga, is also discussed. While different from the traditional system, it was nevertheless based on the comparison of Lithuanian syllable intonations with those of Greek. The Lithuanian accent notation was given its final form by Friedrich Kurschat, who also gave the Lithuanian circumflex sign its present wavy shape, directly and consciously, as he himself admits, derived from Greek (especially from the Greek typefaces current in Germany and France; in Anglophone countries the Greek circumflex often still has the old arc-shaped form). The factor of the common Indo-European heritage in the actual coincidence of Greek and Lithuanian syllable intonations in the end syllables (acute in the nominative, circumflex in the genitive), put forward by Adalbert Bezzenberger, has suffered numerous attacks, notably from Jerzy Kurylowicz; but it has never been convincingly disproved. It still seems that what once was an intuitive – or even incidental – choice of Greek accent signs to mark corresponding Lithuanian accents, indeed reveals a much older and deeper affinity.